Acute oral toxicity study of ethanol extract of Oroxylum indicum leaf in mice - Reduan, Mohd Farhan Hanif; Hamid, Fathin Faahimaah Abdul; Nordin, Muhammad Luqman; Shaari, Rumaizi; Hamdan, Ruhil Hayati; Chung, Eric Lim Teik; Peng, Tan Li; Kamaruzaman, Intan Noor Aina; Noralidin, Noramalina (The Thai Journal of Veterinary Medicine, 2020)
The Oroxylum indicum plant is a herbal plant commonly eaten by the locals in Malaysia while the application of herbal remedies from the plant has been inherited and passed down through generations. However, there is a lack of toxicity profiling of the plant, hence this research aimed to investigate acute oral toxicity of ethanol extract of O. indicum in C57BL/6 male mice at different concentrations, to determine the LD50 of the plant extract. A total of twenty-five mice were randomly assigned into five experimental groups comprising the control (normal saline), vehicle (5% DMSO), low dose (1000 mg/kg bw), medium dose (2000 mg/kg bw) and high dose (5000 mg/kg bw). The extracts were administered in a single oral dose on day 1 and the mice were observed daily for mortality, physiological and behavioural changes throughout the 14 day study period. At the end of the study, vital organs and blood samples were collected to determine the effects of the extract on the relative organ weight, tissue changes and blood profile alterations. No mortality nor behavioural changes were recorded for 2 weeks. Results of the body weight, relative organ weight, haematological and serum biochemistry assessments showed no significant (p>0.05) changes. Nevertheless, there were significant differences in the mean corpuscular volume (MCV), urea and alanine transaminase (ALT) values but the levels were still within the normal range. Histopathological analysis of the liver and kidney tissues also revealed no striking lesions. In summary, this study indicates that O. indicum leaf ethanolic extract up to 5000 mg/kg bw did not cause any toxicological effects in the mice model and is safe to be used for therapeutic purposes.